Effect of amlodipine, a calcium channel antagonist, on gonadal steroid of male wistar albino rats - FC Onwuka; KC Patrick-I wuanyanwu; CK Nnodu; et al (Dove Medical Press, 2010)
FC Onwuka1, KC Patrick-I wuanyanwu1, CK Nnodu1, O Erhabor21Department of Biochemistry, 2Department of Haematology, College of Health Sciences, University of Port Harcourt, Port Harcourt, Rivers State, NigeriaAbstract: This study was carried out to investigate the effect of prolonged intake of calcium-channel blocker amlodipine, an antihypertensive drug on gonadal steroid hormone (testosterone) of male albino rats. Three different concentrations of amlodipine (0.01, 0.02 and 0.03 mg/kg body weight) was administered orally to three different groups (B, C, and D) of experimental male wistar albino rats (n = 8) for six weeks. Group A rats were fed normal diet without amlodipine (n = 8) served as the control. The administration of amlodipine significantly reduced testosterone level in the following order, group A (0.22 ± 0.01) > B (0.18 ± 0.01) > C (0.14 ± 0.01) > D (0.10 ± 0.01). The reduction in testosterone levels corresponded with an increase in the concentration of amlodipine administered to male wistar albino rats. The observation in this study reveals that long-term treatment of male Wistar rats with calcium-channel blocker and antihypertensive (amlodipine) produces a significant reduction in the level of testosterone a hormone associated with decreased ability of men to enjoy sex and to develop good quality erections. There is the need for a large scale study to investigate the potential effect of long-term antihypertensive therapy with amlodipine on sexual dysfunction in men.Keywords: calcium-channel blocker, amlodipine, antireproductive, antihypertensive drugs, gonadal steroid, and low libido